Academic mobbing, an ignored phenomenom and a shored responsibility: A case study at a state university in Costa Rica - Quirós García, Elizabeth (2020)
Mobbing is a negative practice in organizations. This phenomenon consistsin having a person subtly and systematically attacked, directly or indirectly,at least for six months, aspiring to make the victim quit his/her job or forcehim/her into “organizational invisibility.” This research presents an exploratoryand descriptive work on mobbing, its causes and possible consequencesfor the victim and the institution for which s/he works, in this case, theacademia; moreover, it is concerned with the effects it may have on organizationalculture. Besides, this study collected information of two facultymembers who claim to have suffered from mobbing, one of them holding atenure position while the other does not. This case study allowed the researchto understand that the consequences of mobbing are very complex and theyremain with the subjects for many years.